ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb) PADA CABAI MERAH (CAPSICUM ANNUUM L) YANG BEREDAR DI PASAR BATUSANGKAR - Khaira, Kuntum (Sainstek : Jurnal Sains dan Teknologi, 2017)
Research has been conducted to analyze the conten of the heavy metal content of lead (Pb) in red pepper (Capsicum Annuum L) circulating in Batusangkar market. Samples of five red peppers  were  taken from different places in Batusangkar market. The sample was dissolved by using a mixture of sulfuric acid and nitric acid. Furthermore, lead was measured by using atomic absorption spectrophotometry (SSA) at a wavelength of 283.3 nm. The results of the analysis showed that  the lowest lead level of 0.2386 mg / kg and the highest lead level of 0.73642 mg / kg. From  the five samples, it was found that there was one sample whose lead level exceeded the maximum limit set by National Standardization Council of 2009 about maximum limit of heavy metal contamination in food that is 0,5 mg / kg for lead, whereas for 4 other sample the value of lead level is less from 0.5 mg / kg. In addition, from the five samples, one sample did not meet the safe criteria and the other four samples meet the criteria.